Effect of long of landuse and cropping system on soil fertility and cassava yield - Andy Wijanarko; Benito Heru Purwanto (Brawijaya University, 2018)
A study that was aimed to determine the influence of long of land use and cropping systems on soil fertility and yield of cassava conducted at centre of cassava in Sukadana Subdistrict, East Lampung. Survey was conducted to characterize soil fertility due to the long of landuse and cassava cropping system from February to September 2014. Treatments of cropping system and long of land use observed involving: (1) Cassava monoculture for more than 30 years, (2) Cassava monoculture for 10- 30 years, (3) Cassava monoculture for less than 10 years, (4) Intercropping cassava and maize, (5) Intercropping cassava and groundnut, (6) Crop rotation of cassava and maize, and (7) Crop rotation of cassava and groundnut. The results showed that concentration of all macro nutrients of cassava monoculture for more than 30 years was lower than cassava monoculture for less than 10 years including the decrease of 11% of soil pH, 49% of total N , 66% of organic C, 57% of available P, 64% of K, 70% of Ca, 55% of Mg and 37% of CEC. Intercropping or crop rotation of cassava with legume or non-legume increased the soil pH, organic C, total N, K, Ca and Mg and decreased exchangeable Al. The changes in soil chemical and physical properties due to different cropping system affected the yield of cassava. The highest yield of cassava was obtained by crop rotation of cassava and maize, while the lowest was monoculture for more than 30 years. Cassava monoculture grown for 10-30 years or more than 30 years had low soil fertility so that the yield of cassava was also low. The yield of cassava in the rotation system was higher than the intercropping